STUDYING AND IMPROVING TYPES OF ENERGY AND USING THEM IN CHEMICAL TECHNOLOGY - Niyozov Sobir Ahror o‘g‘li; Shodiyev Azimjon Ziyodullayevich; Homidova Gulhayo Rustam qizi (American Journals Publishing, 2023)
Before studying chemical technological processes in depth, it is necessary to know some concepts and laws that lead to understanding the essence of these processes. Depending on the progress of the reaction, the order (mode) in the reactor, some parameters in the equation have a very small value, so they can be ignored. Modeling of chemical processes and reactors. In order to determine the optimal parameters of the technological procedure, apparatus and devices, that is, to optimize the operation of the technological system, a modeling study of chemical processes and reactors is carried out during the design process